Analysis of Eduardo Torroja's Tempul Aqueduct an important precursor of modern cable-stayed bridges, extradosed bridges and prestressed concrete. (1st November 2017) - Lozano-Galant, Jose Antonio; Paya-Zaforteza, Ignacio
Highlights: Eduardo Torroja's Tempul Aqueduct as an important precursor of modern cable-stayed bridges. Critical analysis of the Tempul Aqueduct, its history and its context. Comparison between the results of Finite Element Models and those obtained by Torroja. Abstract: This paper describes a study of the Tempul Aqueduct, one of the first structures designed and built by Eduardo Torroja. At a time when computers did not exist, Torroja's courage and innovation were outstanding. He was in no way constrained by a lack of theoretical knowledge, inadequate materials and the contemporary doubts about cable-stayed structures. In fact, he was able to build one of the world's first prestressed concrete structures, and a precursor to modern cable-stayed and extradosed bridges. This paper briefly reviews the history of the Tempul Aqueduct, gives the results of the analysis of this structure by several Finite Element Models (FEMs), and compares the FEM results to those obtained by Torroja himself. The FEM results confirm the validity of Torroja's conceptual design. The paper also contains a detailed analysis of the influence of the structural system on the behavior of the bridge and the effect of removing the live loads with the aim of providing a better understanding of the context and behavior of the Tempul aqueduct.